Green hub location problem. (May 2019) - Dukkanci, Okan; Peker, Meltem; Kara, Bahar Y.
Highlights: The Green Hub Location Problem (GHLP) is introduced. Vehicle speed and payload are considered to estimate fuel consumption. A nonlinear formulation is developed. The model is formulated by using second order cone programming and perspective cuts. An extensive computational study on the CAB and TR datasets is conducted. Abstract: This paper introduces the green hub location problem that finds the best locations for hubs, assignments of demand nodes to these hubs and speed of trucks/flights so as to route the demand between any origin-destination pairs. The aim of the service provider is to minimize the total amount of emissions that depends on vehicle speed and payload while routing the deliveries within a predetermined service time limit. In this study, we first propose a nonlinear model for this problem, which is then reformulated as a second order cone programming formulation. We strengthen the new model by using perspective reformulation approach. An extensive computational study on the CAB and TR datasets demonstrates the benefits of incorporating green transportation service activities to the classic hub location problems. We also provide insights for the carrier companies by analyzing the solutions with different discount factors, service time limits and number of hubs.